2019
DOI: 10.1063/1.5111169
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectrum of hydrogenated corannulene rim-HC20H10 isolated in solid para-hydrogen

Abstract: Hydrogenated polycyclic aromatic hydrocarbons have been proposed to be carriers of the interstellar unidentified infrared (UIR) emission bands and the catalysts for formation of H2; spectral characterizations of these species are hence important. We report the infrared (IR) spectrum of mono-hydrogenated corannulene (HC20H10) in solid para-hydrogen (p-H2). In experiments of electron bombardment of a mixture of corannulene and p-H2 during deposition of a matrix at 3.2 K, two groups of spectral lines increased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Notably, the reported hydrogenation reactions of corannulene typically occurred under relatively harsh conditions (e.g., electron bombardment, alkyllithium reagents, or alkali metals), and even despite them, reactions typically led to hydrogenation of one or two rim C]C bonds without carbon-carbon bond cleavage. [51][52][53][54][55][56][57] Since the developed conditions (C 20 H 10 /TCNQ/Zn/HCl) required the presence of zinc, we also probed the Clemmensen reduction that uses zinc amalgam and concentrated hydrochloric acid. 58 Mass spectrometry and 1 H NMR spectroscopy studies of reaction products detected the presence of only pristine corannulene and did not detect any traces of corannulene hydrogenation.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the reported hydrogenation reactions of corannulene typically occurred under relatively harsh conditions (e.g., electron bombardment, alkyllithium reagents, or alkali metals), and even despite them, reactions typically led to hydrogenation of one or two rim C]C bonds without carbon-carbon bond cleavage. [51][52][53][54][55][56][57] Since the developed conditions (C 20 H 10 /TCNQ/Zn/HCl) required the presence of zinc, we also probed the Clemmensen reduction that uses zinc amalgam and concentrated hydrochloric acid. 58 Mass spectrometry and 1 H NMR spectroscopy studies of reaction products detected the presence of only pristine corannulene and did not detect any traces of corannulene hydrogenation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, an alternate method to produce hydrogenated PAHs by UV and IR irradiation of C 20 H 10 /Cl 2 /p-H 2 also produced the most stable rim and the second most favorable hub isomer. (Sundararajan et al (2019)).…”
Section: Results and Conclusionmentioning
confidence: 99%
“…To generate SOS, we have applied H atom reactions in solid para -H 2 at 3.1 K. This method was established in the past decade by the groups of Anderson and Lee. It is taking advantage of the phenomenon of quantum diffusion that allows for the efficient movement of the H atoms through the matrix, facilitating H addition and abstraction reactions. Earlier studies in para -H 2 reported the successful hydrogenation of polycyclic aromatic hydrocarbons (PAHs), HONO, isoprene, propene, and pyrrole . Hydrogen abstraction from the isolated molecule by the H atoms could also be detected recently in the case of formamide, methyl formate, and acetamide. As it was shown by these studies, even if a H addition or a H abstraction reaction has a substantial barrier, it can be fast enough at very low temperatures due to H atom tunneling to observe it on the laboratory time scale.…”
Section: Introductionmentioning
confidence: 97%